RISK MANAGEMENT DISCLOSURE: MANAGERIAL OWNERSHIP, RISK MANAGEMENT COMMITTEE, AND CAPITAL STRUCTURE - Annisa Nurbaiti; Fathia Kurnia Muliana (Jurnal Proaksi, 2023)
Risk management within the company is important to avoid risk. This study aims to analyze the influence of managerial ownership, risk management committee, and capital structure on risk management disclosure. The population in this study is financial sector listed on the IDX in 2017-2021. The study used purposive sampling method and determined 27 companies in 5 years, so there were 135 companies sampel. The analysis technique used is panel data regression using Eviews 12. Simultaneously, managerial ownership, risk management committee, and capital structure has a significant effect on risk management disclosure. Partially, managerial ownership has a negative significant effect and risk management committee has a positive effect significant on risk management disclosure. Meanwhile, capital structure do not affect on risk management disclosure.